The mangrove ecosystems on the north coast of Bangkalan, Indonesia, and its potential for mangrove ecotourism - WAHYU ANDY NUGRAHA; AMBARIYANTO AMBARIYANTO; INSAFITRI INSAFITRI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nugraha WA, Ambariyanto A, Insafitri. 2024. The mangrove ecosystems on the north coast of Bangkalan, Indonesia, and its potential for mangrove ecotourism. Biodiversitas 25: 859-868. Mangrove ecosystems have the potential to be used as objects of marine ecotourism, in addition to many ecological functions and one of the main producers in marine fisheries. Bangkalan has a mangrove area of 1500 hectares which has the potential to be used as ecotourism. However, there is no research that analyzes and identifies the suitability index of mangrove tourism along the north coast of Bangkalan, Madura. The purpose of this study was to determine mangrove species, mangrove density, and mangrove tourism suitability index on the north coast of Bangkalan in order to identify the potential of mangrove for eco-tourism. The research was done at 14 stations on the north coast of Bangkalan. Data calculation and analysis were carried out by calculating the thickness of mangroves forest, mangrove species, mangrove density, biota that can be found, tides, accessibility, and infrastucture that were used to calculate mangrove tourism suitability index. The results showed that mangrove thickness in the north coast of Bangkalan were 138 m-864 m. 17 mangrove species were found, with the highest number of species was found in site 13 (Labuhan Education Park) with 14 species. Mangrove density was between 400-3500 trees/ha, with 10 sites in dense category, 2 in average category, and 2 in low category. The results showed that all research sites were included in the sufficient criteria for mangrove tourism. Mangroves in Bangkalan have great potential to develop mangrove tourism since all research sites were included in the sufficient criteria for mangrove tourism.